Keragaman dan Kekerabatan Tanaman Cengkeh (Syzygium aromaticum L.) di Pulau Ternate - Sri Soenarsih; Eko Wahyudiyono; Abd. Rahmat Mandea (Cannarium, 2021)
Cloves (Syzygium aromaticum, syn. Eugenia aromaticum), in English called cloves, is the aromatic dried flower stalks of Myrtaceae family. Cloves are native to Indonesia. In Indonesia, clove species cultivated is Zanzibar, Siputih, Sikotok, and Ambon. The information value of genetic diversity of the population of clove is one of the important considerations in determining conservation and breeding strategies conducted. Identification of diversity and kinship cloves in Ternate Island has never been so necessary to identify the diversity and kinship population of clove in order to add information. The purpose of this study is to determine the diversity of the types of clover on the island of Ternate and to investigate kinship cloves in Ternate Island. The research was conducted on the island of Ternate and sampling sites in the District of North Ternate, Ternate South, Central Ternate, Ternate Island which took place in March 2016 to May 2016. The method used in this research is descriptive method with direct observation of the object being observed, Direct observation on the plant example in the field based descriptors guide cloves. The parameters observed were 21 morphological characters and 24 agronomic characters. Data analyzed using analysis of variance diversity Bartlett and Dunnet test and kekerabatannya processed using data clustering analysis matrix (cluster analysis) and manufacturing methods dendogram with UPGMA method. The results of this study indicate that discovered 11 types of clover on the island of Ternate in the Village Rua (Ambon Panjang), Tonggole (Bogor, Ambon Gemuk, Pink), Sulamadaha (Zanzibar Pangkal Kuning), Foramadiahi (Rica), Marikurubu (Zanzibar, Afo) , Jan (Posi-posi), Fitu (Bendera), and Loto (Putih) with the diversity of the nature shown in several morphological characters. As well as kinship 11 types of clover which shows a close kinship between clove White (PTH) with Afo clove (AFO) is 99.00% while by far the kinship between clove Rica (RICA) with clove Flag (BNDR) is 54.56% and Posi-posi cloves (PSPS) is p53.82%.